Validasi Metode Penetapan Kadar Pengawet Natrium Benzoat pada Sari Kedelai di Beberapa Kecamatan di Kabupaten Tulungagung Menggunakan Spektrofotometer Uv-Vis - Siti Awwalul Amanatur Rohmah; Afidatul Muadifah; Rahma Diyan Martha (Jurnal Sains dan Kesehatan, 2021)
Sodium benzoate is an organic preservative chemical compound which use is permitted if the amount is below the maximum threshold. This research aims to validate the UV-Vis Spectrophotometry method which will be used to determine sodium benzoate levels in soybean milk in 3 sub-districts in the Tulungagung Regency using the UV-Vis Spectrophotometer instruments. Before determining the content, the samples were analyzed qualitatively first using the acid-base titration method. The result of this qualitative analysis of the sample will turn pink if it contains sodium benzoate. Then the sodium benzoate wavelength optimization is carried out in the range of 200-400nm, and the optimum wavelength is 226nm. The method validation process is done by using four parameters namely linearity test, accuracy test, precision test, and LOD&LOQ. Based on the validation of the method, the correlation coefficient (R2) of 0.99563 indicates linear, recovery % is 97.58% in the range of 80-120%, RSD is 0.0454% which is ?2%, LOD is 0.33 ppm, and LOQ of 1.0996 ppm. Based on these results, it can be said that the method used is valid because all parameters meet the specified requirements. Analysis of the determination of levels using a UV-Vis Spectrophotometer instruments at wavelength 226nm using 5 samples, from the five samples obtained average rate of 90.639±0.0406. Analysis of the rate determination using UV-Vis Spectrophotometer instruments at 226nm wavelengths show that sample A has a concentration 92,243±0,039 ppm, sample B is 80,286±0,039 ppm, sample C is 99,04±0,063 ppm, sample D is 101,483±0,025 ppm, and sample E is 80,143±0,038 ppm. The content of sodium benzoate in soybean milk is following the requirements of BPOM RI regulation No.36 of 2013 concerning the maximum limit of food use, the use of sodium benzoate in fruit/vegetable juice products and non-fermented soybean products is 600ppm of food, with ADI 0-5mg/kg body weight.